A case of atrio-esophageal fistula masquerading as upper GI bleed. (2017) - Rali, Parth; Rali, Mayur; Malik, Khalid
Abstract: We represent a fatal case of atrio esophageal fistula that presented as upper GI bleed. The case was complicated by rapidly progressing multi organ dysfunction syndrome and eventual death. This was an iatrogenic complication of an elective procedure.